Sistem Informasi Pengadaan Bahan Baku Berdasarkan Hasil Perhitungan MRP pada UD Eka - Herdeawan, Ahmad Syuyuth; Widodo, Arifin Puji; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
UD Eka is a manufacture company that produce slippers, soles, and shoes. The procurement process of raw materials can be done if the amount of raw materials stock in the warehouse has reached the minimum stock or running out. The company does not do definite calculation in determining quantity of raw materials that have to be ordered. Problems that often experienced by the company is out of raw materials stock at the time of the production process takes place. It might be happen because the absence of raw material requirement plan to avoid the mistake of the amount of raw materials that have to be ordered. Therefore, to overcome the problems, the raw material procurement information system based on the calculation of material requirement planning (MRP) was made. The application can calculate the net requirement of raw material or item (Netting), determine the quantity of raw material or item that will be ordered (Lot Sizing), determine when order must be done (Offsetting), and calculate requirement of raw material or item at lower level. Based on the experimental result conducted by PPIC Managers, this application can be used to plan raw materials and procurement of raw materials. Moreover, this application can generate MRP action reports, raw material requirements reports, raw material acceptance reports, raw material expenditure reports, raw material inventory cards, and supplier performance reports based on actual average leadtime.